2017
DOI: 10.1016/j.enbuild.2016.12.051
|View full text |Cite
|
Sign up to set email alerts
|

Heat-flow variability of suspended timber ground floors: Implications for in-situ heat-flux measuring

Abstract: Reducing space heating energy demand supports the UK's legislated carbon emission reduction targets and requires the effective characterisation of the UK's existing housing stock to facilitate retrofitting decisionmaking. Approximately 6.6 million UK dwellings pre-date 1919 and are predominantly of suspended timber ground floor construction, the thermal performance of which has not been extensively investigated. This paper examines suspended timber ground floor heat-flow by presenting high resolution in-situ h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 21 publications
5
13
1
Order By: Relevance
“…As expected, and as also reported for the floor of a thermal chamber (Pelsmakers et al, 2017), a large spread of U p -values was observed across the floor in this case study in the field. In general, a clear negative association exists between the measured U p -value in a location and its distance from the external perimeter wall: estimated U p -values progressively reduce with the distance from the perimeter wall (Figures 5 and 6).…”
Section: Analysis Results and Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…As expected, and as also reported for the floor of a thermal chamber (Pelsmakers et al, 2017), a large spread of U p -values was observed across the floor in this case study in the field. In general, a clear negative association exists between the measured U p -value in a location and its distance from the external perimeter wall: estimated U p -values progressively reduce with the distance from the perimeter wall (Figures 5 and 6).…”
Section: Analysis Results and Discussionsupporting
confidence: 66%
“…Figure 6 shows that there is no abrupt change after 1 m, but instead a gradual reduction in U pvalues as the distance to the external environment increases (Pelsmakers et al, 2017). It also highlights that when locations were observed in the perimeter zone but not aligned with airbricks in the void below (locations 14-16), U p -values were significantly lower than those in front of airbricks (locations 1, 2, 6-8 and 22) and generally these U p -values were outside the estimated error margins.…”
Section: Analysis Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An example of this is given in a recent study carried out at the Energy House on the subject of suspended timber floors. Significant variation was found across only one room, in which is a simple ventilated timber floor [33].…”
Section: Reliability Of In-situ Measurementsmentioning
confidence: 99%